CREATION OF SPECIALIZED MAPS AND REGISTERS OF OBJECTS UNDER ARTICLE 6, PARAGRAPHS 4 AND 5 OF THE LAW ON THE DEVELOPMENT OF THE BLACK SEA COAST: CREATION OF SPECIALIZED MAPS AND REGISTERS OF OBJECTS UNDER ARTICLE 6, PARAGRAPHS 4 AND 5 OF THE LAW ON THE DEVELOPMENT OF THE BLACK SEA COAST - Niyazi-Yusuf, Mirem (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
The specialized maps and registers are made for the purpose of documenting the spatial position and technical characteristics of the sites under Article 6, paragraphs 4 and 5 of the Law on the Organization of the Black Sea Coast. They also provide information for the development of development schemes and general and detailed development plans, protection of the natural landscape and the sea coast from erosion, abrasion and landslide processes, protection of the cultural and historical heritage, development of investment projects, awarding of concession or renting out sea beaches and solving other tasks.